Ex vivo coronary angiography of a donor heart in the organ care system - Ghodsizad, Ali; Ungerer, Matthias; Karck, Matthias; Bekeredjian, Raffi; Ruhparwar, Arjang (The heart surgery forum, 2012)
The international demand for donor hearts for transplantation is steadily increasing. Thus, longer transportation distances and explantation from sites with limited abilities for preexplantation diagnostics have to be considered. The development of the Organ Care System (OCS) (TransMedics, Andover, MA, USA) may extend the extracorporeal period, with the possibility to constantly evaluate and interact during organ transport. One of the potential advantages of the OCS is the ability to even perform coronary angiography of the donor heart, if a preexplantation angiography evaluation is not possible at the donor hospital and if significant evidence for coronary artery disease in the donor heart becomes known, because of the donor's medical history or after palpation of sclerotic coronary ostia. In this report, we present the first ex vivo coronary angiography evaluation of a potential donor heart that was performed in the OCS. Upon explantation of the donor heart, sclerosis of the left coronary artery was palpated. After reaching the implantation site, a coronary angiography was performed by placing the OCS on a catheterization table and inserting a 6F sheath into the access site of the OCS. A 6F guide catheter was used to intubate the left coronary ostium. Injection of contrast agent led to strong contrast for visualization of the left coronary system. This procedure allowed sufficient assessment of the coronary arteries, which showed a slight diffuse sclerosis without any significant stenosis. This report demonstrates the advantage of the OCS in the complex assessment of donor hearts after explantation. While the donor heart is still in the OCS, not only is it possible to measure metabolic parameters and pressures, but even coronary angiography is feasible. With the increasing international demand for donor organs, such ex vivo examinations might play a more important role, because longer transportation distances can be accepted and organs from suboptimal donors without preexplantation diagnostics may be considered at donor sites with limited diagnostic options.
Gesehen am 07.06.2018